FAKTOR-FAKTOR YANG MEMENGARUHI KEJADIAN KELUHAN COMPUTER VISION SYNDROME PADA MAHASISWA FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA SELAMA PEMBELAJARAN JARAK JAUH - Arief Fadhilah (2022)
Computer vision syndrome or known as CVS is a health problem in the eyes caused by an extended period of time spent on a computer, tablet or cellphone screen. Online learning from home increases the risk of CVS complaints in students. Symptoms commonly felt in patients with CVS are red eyes, headaches, and itchy eyes. The purpose of this study was to determine the relationship between individual factors, environmental factors and work equipment factors with the incidence of computer vision syndrome complaints in students. This research was a quantitative study using a cross-sectional design with a sample size of 310 students. These samples were selected by using a proportionate random sampling technique. The results of this study indicate the factors associated with the incidence of computer vision syndrome complaints, were duration of use of electronic devices (p-value=0.000), use of spectales (p-value=0.012), duration of rest (p-value=0.000), sources of room lighting (p-value=0.032) and viewing distance to the monitor (p-value=0.003). Therefore, it is recommended to apply preventive measures to minimize incidents with the 20-20-20 rule. Every 20 minutes of using an electronic device or staring at a monitor screen to see something else 20 feet away for 20 seconds. Keywords: Computer Vision Syndrome, College Student